Role of salivary vascular endothelial growth factor (VEGF) in palatal mucosal wound healing. Issue 4 (11th June 2013) - Keswani, Sundeep G.; Balaji, Swathi; Le, Louis D.; Leung, Alice; Parvadia, Jignesh K.; Frischer, Jason; Yamano, Seiichi; Taichman, Norton; Crombleholme, Timothy M.
Abstract The mucosa of alimentary tract heals more rapidly than cutaneous wounds. The underlying mechanisms of this enhanced healing have not been completely elucidated. Constant exposure to salivary growth factors has been shown to play a critical role in mucosal homeostasis and tissue repair. Angiogenesis also has an essential role in successful wound repair. One of the main angiogenic growth factors, vascular endothelial growth factor (VEGF), has a pleiotropic role in tissue repair via neovascularization, reepithelialization, and regulation of extracellular matrix. We have previously reported a critical role for salivary VEGF in bowel adaptation after small bowel resection. We hypothesize that salivary VEGF is an essential stimulus for oral mucosal tissue repair, and use the murine palatal wound model to test our hypothesis. In a loss‐of‐function experiment, we removed the primary source of VEGF production through selective submandibular gland (SMG) sialoadenectomy in a murine model and observed the effects on wound closure and neovascularization. We then performed a selective loss‐of‐function experiment using the protein VEGF‐Trap to inhibit salivary VEGF. In a gain‐of‐function experiment, we supplemented oral VEGF following SMG sialoadenectomy. After SMG sialoadenectomy, there was significant reduction in salivary VEGF level, wound closure, and vessel density. Lower levels of salivary VEGF were correlated with impaired neovascularization and reepithelialization. The selective blockade of VEGF using VEGF‐Trap resulted in a similar impairment in wound healing and neovascularization. The sole supplementation of oral VEGF after SMG sialoadenectomy rescued the impaired wound healing phenotype and restored neovascularization to normal levels. These data show a novel role for salivary‐VEGF in mucosal wound healing, and provide a basis for the development of novel therapeutics aimed at augmenting wound repair of the oral mucosa, as well as wounds at other sites in the alimentary tract.